Effect of Continuous Renal Replacement Therapy on Multi-dimensional Serum Biomarkers (IL-4, Presepsin, NGAL, PD-L1, IL-10, Ang-2, sTM, histones, mtDNA, ADM, and suPAR levels ) and Clinical Symptoms in Patients with Sepsis: CRRT effects on multi-dimensional biomarkers in sepsis - Shen, Tao (Journal of Medical Biochemistry, 2026)
Objective: To investigate the effects of continuous renal replacement therapy (CRRT) on traditional and novel multi-dimensional serum biomarkers including inflammatory cytokines, immune regulation markers, endothelial injury markers, cellular damage indicators, and clinical symptoms in patients with sepsis. Method: A retrospective collection was conducted on 116 sepsis patients treated with CRRT in the hospital from March 2019 to June 2024 as the observation group; 219 sepsis patients who received conventional treatment during the same period were matched with propensity score in a 1:1 ratio, and 116 patients were selected as the control group. Two groups of patients were observed and compared for TNF-α, IL-4, CRP, Presepsin, IL-6, NGAL, PD-L1, IL-10, mHLA-DR, Ang-2, sTM, histones, mtDNA, ADM, suPAR, and clinical symptom related indicators after treatment. COX regression analysis was utilized to investigate the influencing factors of 28 d survival in sepsis patients after treatment. Results: After treatment, the TNF-α, IL-4, CRP, Presepsin, IL-6, NGAL, PD-L1, IL-10, Ang-2, sTM, histones, mtDNA, ADM, and suPAR levels in the observation group were significantly lower than those in the control (*p*
Keywords: Sepsis; Continuous renal replacement therapy; Inflammatory cytokines; Presepsin; Immune checkpoint; Endothelial injury; Cellular damage; Prognosis